The Decolonization of Colonial Archives on Indigenous Political Resistance in the Maluku Islands - Aji Deni; Agusmawanda Agusmawanda; Sosiawaty Sosiawaty; Aswir Badjoda (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
Colonial archives on the Maluku Islands heavily feature Eurocentric biases that marginalize indigenous perspectives, thereby distorting the history of local resistance and heroism. This study examines how decolonial archival practices dismantle embedded colonial epistemologies and restore marginalized indigenous voices. Employing a systematic review of interdisciplinary literature, this research analyzes the integration of local oral histories, indigenous traditions, and cultural expressions with conventional colonial archival sources. The synthesis yields a nuanced, alternative narrative of Malukan resistance through three distinct dimensions, archiving hidden indigenous agency overlooked in colonial historiography; establishing participatory methodologies that engage local communities in historical knowledge production; and formulating institutional critiques against archives and museums acting as prolonged instruments of colonial power. Ultimately, decolonizing archives in Maluku drives restorative justice and serves as an essential framework for constructing a more inclusive, pluralistic, and equitable Indonesian historiography.